Combined oesophageal atresia with upper pouch fistula and meconium peritonitis - Andre Theron; Jerome Loveland; Jaishree Naidoo; Anne Theron (Wolters Kluwer Medknow Publications, 2012)
Upper pouch tracheoesophageal fistula occurs is less than 1% of all oesophageal atresia variants. Meconium peritonitis is a rare neonatal condition with an incidence of 1:30 000 live births. In this case report, we describe the presentation, clinical findings and management of a patient diagnosed with an oesophageal atresia with upper pouch fistula as well as meconium peritonitis. To the best of our knowledge, this is the first case such as this described in published literature.